The groESL Chaperone Operon of Lactobacillus johnsonii - Walker, D. Carey (American Society for Microbiology, 1999)
The Lactobacillus johnsonii VPI 11088 groESL operon was localized on the chromosome near the insertion element IS1223. The operon was initially cloned as a series of three overlapping PCR fragments, which were sequenced and used to design primers to amplify the entire operon. The amplified fragment was used as a probe to recover the chromosomal copy of the groESL operon from a partial library of L. johnsonii VPI 11088 (NCK88) DNA, cloned in the shuttle vector pTRKH2. The 2,253-bp groESL fragment contained three putative open reading frames, two of which encoded the ubiquitous GroES and GroEL chaperone proteins. Analysis of the groESL promoter region revealed three transcription initiation sites, as well as three sets of inverted repeats (IR) positioned between the transcription and translation start sites. Two of the three IR sets bore significant homology to the CIRCE elements, implicated in negative regulation of the heat shock response in many bacteria. Northern analysis and primer extension revealed that multiple temperature-sensitive promoters preceded the groESL chaperone operon, suggesting that stress protein production in L. johnsonii is strongly regulated. Maximum groESL transcription activity was observed following a shift to 55°C, and a 15 to 30-min exposure of log-phase cells to this temperature increased the recovery of freeze-thawed L. johnsonii VPI 11088. These results suggest that a brief, preconditioning heat shock can be used to trigger increased chaperone production and provide significant cross-protection from the stresses imposed during the production of frozen culture concentrates.